2022
DOI: 10.1088/1748-9326/ac7063
|View full text |Cite
|
Sign up to set email alerts
|

Grassy–herbaceous land moderates regional climate effects on honey bee colonies in the Northcentral US

Abstract: The lack of seasonally sustained floral resources (i.e., pollen and nectar) is considered a primary global threat to pollinator health. However, the ability to predict the abundance of flowering resources for pollinators based upon climate, weather, and land cover is difficult due to insufficient monitoring over adequate spatial and temporal scales. Here we use spatiotemporally distributed honey bee hive scales that continuously measure hive weights as a standardized method to assess nectar intake. We analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…Our findings likewise indicate that climate is closely associated with honey production, likely through climate effects on floral resources. A recent study on colony productivity across the North Central US likewise identified climate conditions as the most important factor for describing honey bee colony weights, as compared to land use and annual weather [22]. Similar to our findings, the authors describe greater colony weight gain in the cool, dry regions of the study [22].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings likewise indicate that climate is closely associated with honey production, likely through climate effects on floral resources. A recent study on colony productivity across the North Central US likewise identified climate conditions as the most important factor for describing honey bee colony weights, as compared to land use and annual weather [22]. Similar to our findings, the authors describe greater colony weight gain in the cool, dry regions of the study [22].…”
Section: Discussionsupporting
confidence: 88%
“…A recent study on colony productivity across the North Central US likewise identified climate conditions as the most important factor for describing honey bee colony weights, as compared to land use and annual weather [22]. Similar to our findings, the authors describe greater colony weight gain in the cool, dry regions of the study [22]. Warm and cool climates are likely not intrinsically supportive of floral resources.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The amount of food collected by bees in each trip m allows for a better assessment of foraging difficulty and thus of environments that can best support beekeeping operations [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Directly measuring the number of forager bees is difficult, but the use of new technologies provides opportunities to estimate them from more accessible data [12,21]. Recently developed affordable and precise balances can easily be fitted to hives in the field to study the longterm weight changes [22] and shorter within-day weight variations of hives [12,23]. Withinday hive weight variations are clearly visible and exhibit similar patterns that are consistent across multiple day as shown in Fig 1 . In the morning, rapid weight loss occurs because foragers leave the hive [24].…”
Section: Introductionmentioning
confidence: 99%